Sectoral Activities Programme Working Papers Petroleum Training in Algeria and Nigeria - McLin, Jon (International Labour Office, 1989)
This book analyse and disseminate information on Successful training experiences in the Petroleum industry made by member states.
Keywords: International Labour- Petroleum industry and trade